PERPAJAKAN DI ERA EKONOMI DIGITAL: INDONESIA, INDIA DAN INGGRIS - Yanis Ulul Az'mi (Universitas Pakuan, 2018)
The development of new technology and diverse consumer demand has increased the digital retail industry today. This also affects the way buyers / consumers get the goods and services they want. Consumers turn to e-commerce and cellular to make purchases that are usually done physically. This change in shopping style has been driven largely due to the emergence of many market places and platforms. This change will also have effect on the taxation of the transaction. The Government of India applies the Equalization Levy Rules (EQL) scheme which is categorized as PNBP (Non-Tax Revenues). While in the United Kingdom there is a Diverted Provit Tax (DPT) scheme. Whereas Indonesia has no more specific rules, there is only a Circular (Surat Edaran) that regulates the Affirmation of Tax Regulations on e-Commerce Transactions, namely SE / 62 / PJ / 2013 tax regulations e-commerce follows the income tax law and value added tax.